Force distribution determines optimal length of β-sheet crystals for mechanical robustness - Xiao, Senbo; Stacklies, Wolfram; Debès, Cédric; Gräter, Frauke (Soft matter, 2011)
Atomistic models of β-sheet crystals with varying number of alanines were mechanically tested in Molecular Dynamics simulations. The gain in mechanical robustness per residue is maximal for strands that are 8 residues long, because the external force is efficiently deflected into neighbouring strands over the distance they span, rendering 8 residues a mechanical optimum for a semi-crystalline material like silk.
First published: 31 Aug 2010
Gesehen am 05.12.2022